Effect of self and peer assessments on mathematics learning achievement - Baiduri, Baiduri (Al-Jabar: Jurnal Pendidikan Matematika, 2022)
Assessment is an essential part of the learning process in higher education. As a result, the assessment should involve students in addition to lecturers. The purpose of this study is to examine the self and peer assessments on the answers to midterm and final-semester exams given by lecturers and their relationship with student achievement. The participants in this study were 114 fifth-semester mathematics education students who took differential equations courses. Data were gathered from student assessment scores on the middle and final test and student achievement in the lecturer's differential equations courses. The data were analyzed using descriptive statistics and an independent sample t-test to describe the self and peer assessments. Pearson correlation analysis was also used to describe the relationship between self and peer assessment and learning achievement. The study revealed no significant difference between self and peer assessments, both midterm and final semester assessments. The midterm assessment said that the average self-assessment was higher than peers. Meanwhile, the assessment average scores obtained in the semester's final exam were nearly identical between the two assessors. There is a positive and significant correlation with a high level of self and peer assessments, both in the midterm and final semester, and a positive and significant correlation with a moderate level of self and peer assessments with learning achievement. These findings can be used as a basis for lecturers to consider when involving students in assessing student achievement.